Compatibility of Sustainable Development Goals (SDGs) with Maqasid al-Shariah: Are there any Missing Goals - Hafiz Abdur Rehman; Hamid Hasan; Malik Muhammad (Islamic Banking and Finance Review, 2021)
After the partial success of Millennium Development Goals (MDGs-2015), the United Nations Development Programme (UNDP) introduced the Sustainable Development Goals (SDGs-2030) for the next fifteen years. The seventeen SDGs have been adopted by almost all member countries of the UN. These goals mainly cover three dimensions of sustainable development, namely social, economic and environmental, and they aim to ensure the sustainability of resources and life on earth. Muslims constitute more than 1/4th of the total world population and there are fifty-seven sovereign states in the world with a Muslim majority. This paper is an attempt to evaluate SDGs in the light of Islamic teachings pertaining to environmental sustainability and human development. The Islamic vision of peace, progress and its continuity was expounded by early Muslim thinkers in the form of Maqasid al-Shariah. The objective of this paper is to show how SDGs are compatible with Maqasid al-Shariah. It also identifies the gaps in the existing SDGs in the light of Islamic teachings. This study used primary Shariah sources to show the similarities between SDGs introduced by UNDP and the axioms of Maqasid al-Shariah. Additionally, the shortcomings of SDGs when compared with the axioms of Maqasid al-Shariah are identified. These shortcomings are related to justice, ethics, and humanity. The improvements suggested in this study may make SDGs universal. Hence, this is a distinctive study which has attempted to augment the globally recognized socio-economic objectives of SDGs. Consequently, it allows for a better understanding of SDGs and ensures their applicability in Muslim societies.KeywordsMaqasid al-Shariah (MS), Missing Goals (MS), Sustainable Development Goals (SDGs)